Perbandingan Kurikulum Pendidikan Sejarah di Rusia dan Indonesia - Jumardi Jumardi (Program Studi Pendidikan Sejarah Pascasarjana UNJ, 2015)
Learning of history very real associated with human life itself. Learning the history of studying thehuman role in the nation’s history and history itself . Learning curriculum history becomes important instudying the role of every human being . This should be reviewed when learning materials and learningoutcomes are not proportional . The educational system of a country determines how a curriculum isapplied to all subjects . Comparing a learning curriculum Indonesian history becomes necessary to obtaina picture of how the teaching of history in Indonesia and the Russian State history teaching curriculum. Models of teaching history in Indonesia using the spiral model ( repetition ) while Russia using linearmodels . Learners and citizens of Russia have the pride of the history of his country.